Effect of Smoking on Prognostic Factors of Transitional Cell Carcinoma of the Bladder - Mohseni, Mohammad Ghasem; Zand, Saeed; Aghamir, Seyed Mohammad Kazem (Urology Journal, 2009)
Purpose: This study was conducted to evaluate the effects of smoking on the clinical characteristics and growth trend of transitional cell carcinoma (TCC) of the bladder. Materials and Methods: In a retrospective case-control study from February 2000 to March 2003, patients with TCC of bladder, referred to our clinic, were selected and divided into high-grade and low-grade groups. Groups were matched for other known risk factors and the effect of smoking on size, number, and presenting grade of TCC in each group was evaluated. Results: A total of 185 patients, with a mean age of 65.1 Â± 14.0 year, were included in this study, of whom 3